Interaction experiences in mobile augmented reality - Nazri, N.I.A.M. (Penerbit UTM Press, 2015)
The world of mobile computing has been advancing at a tremendous rate over the past numbers of years and is set to continue well in the future. The vast majority of interaction between the user and mobile of today makes use of touch screen displays that have now become the de-facto standard in all smart phones. This paper presents a mobile Augmented Reality (AR) application making use of different kinds of interaction techniques to investigate user experience and the usefulness of the AR technology. Comparisons are drawn with a ported version of the application that makes use of the more traditional touch screen interaction paradigm (2D), thus allowing users to accurately gauge their interaction style preference. The application also makes use of finger-based gesture, auditory (3D sound) and haptic based feedback to ground the user and create a richer experience. Our results shows that though the user feels that 2D interaction is easy to use, they find that using gesture based AR interaction is more fun and enjoyable in this mobile AR application. Â© 2015 Penerbit UTM Press. All rights reserved.